Manusia Menurut Teologi John Wesley dalam Membangun Toleransi dan Solidaritas Gereja Methodist Indonesia (GMI) di Wilayah I - Hutauruk, Runggu; Pintor Marihot Sitanggang; Riris Johanna Siagian (Majalah Ilmiah METHODA, 2025)
The doctrine of the Imago Dei is a fundamental Christian concept regarding human beings, which can be generally divided into three categories: capacity, function, and relationality, which distinguishes them from other creation. Capacity concerns the inherent abilities of humans, such as reason, emotion, and will. Function concerns humans as social beings and as stewards of themselves, others, and other creations. Relationality addresses the relationship with God as the source of life, both physical and spiritual. In relation to other creations, the Bible teaches that humans are noble creatures, given the image of God and stewardship over nature and other creations. Human dignity and worth are due to the image of God within them. This is a crucial concept for human dignity and human rights. In John Wesley's doctrine, man as the Imago Dei consists of a natural image; a political image; and a moral image. The natural image of God in man includes free will, intellect, and eternity. God gave man free will, but this free will is responsible, unlike the free will of animals, where humans can distinguish between right and wrong while animals cannot. Therefore, human freedom of will demands responsibility. Then, humans are given an intellect that exceeds that of other creations of God on earth. Humans with their intellect (reason) can understand the truth.